Excessive load - Poutanen, Tuomo; Pursiainen, Sampsa; Länsivaara, Tim (Frontiers in Built Environment, 2023)
Sometimes structural loads are excessively high, and a decision must be made if intervention, either the excess load removal or strengthening of the structure is needed. This issue has been addressed earlier in the retrofitting literature. However, equations for excess load calculation are not presented. This article includes equations based on the full probabilistic reliability model for the failure probability of excessive load of three materials steel, timber, and concrete. Failure probabilities are given as a function of the load designed for the full capacity according to the Eurocodes. Safe excessive loads, i.e., loads with a failure probability less than 1/1500 are given, too. The load combination is a critical issue in this study. There are many options for the load combination which vary regarding the dependent vs. independent load combination, dependent vs. independent reliability calculation, the reference time, and the reference reliability. The conclusion is that the loads should be combined dependently, reliability should be calculated dependently, the reference time is 50 years, and the reliability is the 50-year reliability. We stress that the reliability of steel structures is questionably low in the current Eurocodes.